Studies in law, politics, and society - Sarat, Austin (Emerald Publishing Limited, 2017)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest edition of this highly successful research series, articles examine a diverse range of legal issues and their impact on and intersections with society.
Keywords: Sociological jurisprudence.; Law -- Political aspects.; Political sociology.; elektronické knihy; electronic books